Constructing an Imaginary Wall in the Ocean: A Technical Cartography Study on the Delimitation of Maritime Boundaries in the Provinces of South Sumatra and Bangka Belitung Islands Based on GIS - Agung Kurniawan; Nurul Khakhim; Karen Slamet Hardjo; Agus Iwan Santoso; Widodo Setiyo Pranowo (ASEAN Journal on Science and Technology for Development, 2021)
Marine management areas in Indonesia can be claimed 12 nautical miles from the coastline by regional governments, according to Law 23 of 2014. However, in reality, there are many provinces whose distances to other provinces are fewer than 2 × 12 nautical miles, necessitating that they be delimited fairly and proportionally. The provinces of South Sumatra and Bangka Belitung Islands are such an example. The absence of clear boundaries drawn on the national map of Indonesia was the fundamental problem and focus of this study, owing to the need for delimitation of regional sea boundaries. The delimitation method used to obtain the median line was the equidistance principle using the basepoint to basepoint approach and baseline to baseline, within the consideration of the coastline proportion. Small islands are taken into account as a highly influencing factor and cause of the deviation from the pure median line. The median line results based on the basepoint to basepoint approach showed an area of the ocean as large as 7426.24:5973.41 km2, considering the coastline proportion. Meanwhile, with the baseline to baseline approach, resulting area was 7430.65:5956.13 km2 (South Sumatra:Bangka Belitung Islands). The equidistance principle is a comprehensive method for calculating the median line, as shown in this research.